HUBUNGAN TINGKAT PENGANGGURAN DAN PERTUMBUHAN EKONOMI DALAM PERSPEKTIF ISLAM - Putri, Silvia Usmayanti; Habiba, Meilany Pramesti; Falefy, Kurnia Yulia Ayu; Mawarni, Nadia Hera; Hidayati, Amalia Nuril (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2025)
Unemployment is one of the major issues in the economy, particularly in developing countries such as Indonesia. This journal examines the relationship between unemployment and economic growth from an Islamic economic perspective. In Islam, unemployment is viewed as an injustice that affects not only the economy but also moral and social aspects. This study adopts a qualitative approach through literature review. The findings indicate that high unemployment rates can hinder economic growth, increase social burdens, and exacerbate inequality. In the Islamic context, the solution to unemployment involves not only technical government policies but also the optimization of Islamic financial instruments such as zakat, infāq, ṣadaqah, and waqf. Furthermore, Islam promotes inclusive and just economic growth by encouraging job creation aligned with sharia principles. Therefore, synergy between government, society, and the Islamic economic system is essential to reduce unemployment and foster equitable economic development.